Domain Kesadaran Risiko Penyakit Kardiovaskular dengan Aktivitas Fisik pada Mahasiswa Keperawatan - Wella Meitri; Anita Mirawati; Yulvi Hardoni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the relationship between the domains of cardiovascular disease risk awareness, including knowledge, perceived risk, perceived benefits and intentions to change behavior, and healthy eating intentions, and physical activity among nursing students. The study employed a correlational analytic design with a cross-sectional approach. The results showed that all domains of cardiovascular disease risk awareness were significantly associated with physical activity (p<0.05), although the correlation strengths ranged from very weak to weak. Positive correlations were found for knowledge (r=0.106; p=0.041), perceived benefits and intentions to change behavior (r=0.230; p<0.001), and healthy eating intentions (r=0.176; p=0.001), whereas perceived risk showed a very weak negative correlation with physical activity (r=-0.110; p=0.034). Among all domains, perceived benefits and intentions to change behavior demonstrated the strongest association with physical activity. In conclusion, knowledge of cardiovascular disease alone is insufficient to encourage nursing students to engage in physical activity. Keywords: Cardiovascular Disease Risk Awareness; Nursing Students; Perceived Risk; Physical Activity